Ricardo's Views on Monetary Questions - Sayers, R. S. (Quarterly Journal of Economics, 1953)
I. Introduction, 30. — II. The meaning of depreciation, 31. — III. The cause of depreciation, 33. — IV. Resumption and a choice of standard, 36. — V. The Ingot Plan, 37. — VI. The fall in prices after resumption, 40. — VII. Attitude towards Bank of England, 43. — VIII. Conclusion, 46.